FROM STRUCTURE TO REALITY : LAW ENFORCEMENT , INEQUALITY FUNCTIONAL , AND JUSTICE FOR RESIDENT - Irfandi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Study This aiming For analyze inequality between law normative and practical its implementation in system Indonesian law , as well as to study the impact to justice social and awareness law citizens . This article also explores the role of Citizenship Education in to form character critical , fair and conscious citizens​ law . In the research This the method used is approach qualitative descriptive with type studies library , relying on secondary data from literature academic , documents law , and reports institution independent . The results of the study show that inequality enforcement law due to low integrity institution justice , intervention power , and social bias to group vulnerable . The phenomenon of dualism of law causes law lost universal and changing nature become tool discriminatory power . Therefore​ that , Citizenship Education own position strategic in to plant mark justice , awareness law , and bias towards groups marginal , in order to create a more society fair and democratic .